Analisis Sudut Kemiringan Lempeng Subduksi di Selatan Jawa Tengah dan Jawa Timur Berdasarkan Anomali Gravitasi dan Implikasi Tektonik Vulkanik - Dwi Indriana, Rina (BERKALA FISIKA, 2008)
Gravitation anomaly research had been done to predict the subduction dip and model. The gravitation research covered East and Central Java, Indonesia. Upward continuation used for regional anomaly mapping. Two dimension modeling from each cross-sectional used grav2poly or grav2dc. From 2D model subduction dip was calculated. The research result were subduction dip various between 3,40 to 8,20. There is a suggestion that low magnitude of dip correlated with volcano activity and high magnitude of dip correlated with some depresstion zone. Key word: subduction zone, subduction dip, gravitation modeling